Practical application of technical qualification of innovative wave and tidal designs (Proceedings of the European Wave and Tidal Energy Conference, 2025)
World Class Maintenance (WCM), a network of asset owners, service suppliers and research institutions, selected  our company Bilfinger to independently qualify different innovative technologies following IEC TS 62600-4:2020 within the O4S project. The technology qualification is a process for identifying and providing evidence that a new innovative technology (or an existing technology in new conditions) will be functionally reliable within specified limits and with reasonable confidence. To achieve that goal, qualification activities must identify the technology’s failure modes through tests, computations, or analyses. Our objective was thus to assess each project's current Technology Readiness Level (TRL) and outline steps to advance to the next level, ultimately achieving the highest TRL indicating the technology’s readiness for commercial deployment. The offshore solutions to be qualified were: Dutch Wave Power’s (DWP) wave energy converter, Water2Energy’s (W2E) and Tocardo’s tidal energy converters, FLASC’s Hydro-Pneumatic offshore Energy Storage system and Oceans of Energy’s (OoE) offshore solar system. All these projects either enable the conversion of renewable energy into electrical power or  store and supply consistent electricity. Various technology concepts were already existing. Thus all the developers except OoE, aimed to improve earlier designs using innovative and cost efficient solutions. First we summarized all the functional requirements i.e. a technical qualification basis was defined. We then determined the overall technical maturity by using qualitative questionnaires. With  the technology developers, we proceeded to make a detailed functional decomposition of each design. This enabled us to determine and assess the impact of the integration readiness level (IRL) on the TRL levels of the subsystems/ components. We also determined the novelties and the uncertainties in the designs by characterizing the technology into four classes to verify the need of a risk assessment. Afterwards, we performed an extensive Failure Mode Effect & Criticality Analyses (FMECA) including a risk analysis to identify the critical elements and possible risk mitigating actions. Additionally for W2E and DWP, we conducted Reliability, Availability and Maintainability (RAM) analyses based on input from the FMECA study and Bilfinger subject matter experts. For Tocardo and FLASC, implementation plans  for setting up digital twins were developed. Based on all findings, we wrote a technology qualification appraisal report and reviewed each project’s Technology Qualification Plan (TQP). For OoE, an elaborated OPEX model for maintenance and a Strategic Asset Management Plan (SAMP) were developed creating targeted Asset Management goals in the Operations and Maintenance phase. Overall the results showed that the global design maturity levels were as initially expected. To attain the next TRL, additional testing but mostly extra design studies were required. The FMECA’s helped to detect in an early stage, potential component-level design improvements and showed that early filtering based on criticality should preferably be avoided due to the experimental phase they’re in. The outcome of the RAM analyses and the integration of SCADA and control systems to designs, highlighted the importance of including monitoring and predictive strategies within the FMECA. Concluding, adopting a pragmatic way of working and encouraging synergies between designers, contributes to successful renewable energy solutions.